ANALISIS PROBLEMATIKA KEKERASAN SEKSUAL DI PONDOK PESANTREN - Suparjon Suparjon (Smart Education, 2025)
Abstract: Sexual violence in Islamic boarding schools is a complex and worrying issue, considering that Islamic boarding schools are Islamic educational institutions which are supposed to be safe and educational places for students. This phenomenon is influenced by various factors, such as abuse of authority, patriarchal culture, lack of education about sexual violence, and minimal supervision and regulation of Islamic boarding schools. Cases of sexual violence are often difficult to uncover due to social pressure, threats from perpetrators, and the stigma attached to victims. This research aims to identify the root of the problem of sexual violence in Islamic boarding schools, analyze the causal factors, and formulate strategic steps to prevent and handle these cases. The method used involves literature review, case data analysis, and interviews with related parties. The research results show that public openness in discussing this issue, increasing government supervision, and implementing a safe reporting system are important steps in resolving the problem of sexual violence in Islamic boarding schools. With a holistic approach, it is hoped that this research can contribute to creating an Islamic boarding school environment that is safe, inclusive, and free from sexual violence, so that Islamic values and public trust in Islamic boarding schools can be maintained. Keyword: Problems, Sexual Violence, Islamic Boarding Schools Abstrak: Kekerasan seksual di pondok pesantren merupakan isu yang kompleks dan memprihatinkan, mengingat pesantren adalah lembaga pendidikan Islam yang seharusnya menjadi tempat aman dan mendidik bagi para santri. Fenomena ini dipengaruhi oleh berbagai faktor, seperti penyalahgunaan otoritas, budaya patriarki, kurangnya edukasi tentang kekerasan seksual, serta minimnya pengawasan dan regulasi terhadap pesantren. Kasus-kasus kekerasan seksual sering kali sulit terungkap karena tekanan sosial, ancaman pelaku, dan stigma yang melekat pada korban. Penelitian ini bertujuan untuk mengidentifikasi akar masalah kekerasan seksual di pesantren, menganalisis faktor-faktor penyebabnya, serta merumuskan langkah-langkah strategis untuk mencegah dan menangani kasus tersebut. Metode yang digunakan melibatkan kajian literatur, analisis data kasus, serta wawancara dengan pihak-pihak terkait. Hasil penelitian menunjukkan bahwa keterbukaan masyarakat dalam membahas isu ini, peningkatan pengawasan pemerintah, dan implementasi sistem pelaporan yang aman merupakan langkah penting dalam menyelesaikan problematika kekerasan seksual di pesantren. Dengan pendekatan yang holistik, penelitian ini diharapkan dapat memberikan kontribusi dalam menciptakan lingkungan pesantren yang aman, inklusif, dan bebas dari kekerasan seksual, sehingga nilai-nilai Islam dan kepercayaan masyarakat terhadap pesantren dapat terjaga. Kata kunci: Problematika, Kekerasan Seksual, Pesantren